Sistem Pendukung Keputusan Rekomendasi Penempatan Magang Mahasiswa ( MAGMA ) Program Studi Rekayasa Keamanan Siber Berbasis Website Menggunakan Metode Forward Chaining - Maharani, Clarissa Monique; Perdana, Danis Putra; Wulan, Puspa Ira Dewi Candra; Syarif, Khamarudin (Jurusan Informatika Universitas Jenderal Achmad Yani, 2023)
The problem that often occurs in student internships is the mismatch between the type of work and student skills due to lack of information and literacy. With this problem, an expert system innovation was created as a decision-making tool for students, companies, and internship provider institutions. Decision support system is a computer development system that uses various sources of models to solve existing problems. This research is realized by implementing an expert system using the forward chaining method to recommend the right internship place for cyber security engineering study program students. The goal is to develop an intelligent tool that can accurately identify internship companies or institutions based on specified qualifications and optimize student placement according to certain skills, interests and requirements. Data was collected through distributing closed questionnaires to 21 students of the cyber security engineering study program as a reference in system design. Based on the test results of the comparison between expert system logic and manual logic, this system has a 100% accuracy rate.